A short proof of the wonderful lemma. Issue 3 (18th May 2017) - Chudnovsky, Maria
Abstract: The Wonderful Lemma, that was first proved by Roussel and Rubio, is one of the most important tools in the proof of the Strong Perfect Graph Theorem. Here we give a short proof of this lemma.